Efficacy of Streptomyces melanosporofaciens strain X216 at controlling clubroot disease on oilseed rape - Ding, Lin; Zhou, Hu; Liang, Hai-di; Tan, Lin; Zhao, Hui; Chen, Xiao-jun; Ren, Zuo-hua (Frontiers in Microbiology, 2023)
Oilseed rape (Brassica napus L.) is highly susceptible to infection from the soilborne pathogen Plasmodiophora brassicae Woronin that causes clubroot disease and deleteriously affects production throughout the world. In this study, biological control resources were explored by isolating 237 strains of bacteria from fields of oilseed rape using the gradient dilution coating method. A strain with strong antagonistic ability was screened using a plate confrontation test and designated X216. It was identified as Streptomyces melanosporofaciens owing to its morphological characteristics and 16S rRNA gene sequence. This study also examined the lethality of strain X216 to the resting spores of P. brassicae, its influence on infection in root hairs, and its ability to control clubroot on oilseed rape. The corrected lethality rate on resting spores after strain X216 had been used for 14 days was 56.59%±1.97%, which was significantly higher than the use of 75% of the fungicides chlorothalonil WP and 20% Fluazinam SC. Significantly fewer root hairs were infected after this treatment. A pot test showed that X216 was 62.14% effective at controlling the disease, which was not significantly different from that of the fungicide 100 g L -1 cyazofamid SC diluted 1,000-fold but significantly higher than those of 75% chlorothalonil and 50% carbendazim WP. Strain X216 controlled 43.16% of the incidence of clubroot in the field, which could significantly reduce the disease index of oilseed rape clubroot.Therefore, strain X216 is promising to study for the biological control of oilseed rape clubroot.